Are There Myths on Road Impact and Transport in Sub-Saharan Africa? - (:unkn) unknown (My University, 2013)
As planned large investments in road infrastructure continue to be high on the agenda of many African countries, only few of these countries have actually ammended their investments strategy. In many cases, there seems to be a preference for a status quo that can easily be explained by political economy factors driving the policies in the sector. This paper first presents data on the state of roads in Sub-Saharan Africa (length, density, condition) as well as on investments in the sector over the last decades. It then demonstrates how most countries' strategies are based on some misperceptions and recommends some changes to improve the developmental impact of roads investments. Better prioritization of investments, better procurement and contract management, better projects implementation and better monitoring are still needed, in spite of the efforts observed in the last 10 years.
Keywords: African Research